2004
DOI: 10.1353/pla.2004.0070
|View full text |Cite
|
Sign up to set email alerts
|

Problem-Based Learning in the Library: Evolving a Realistic Approach

Abstract: This article examines issues encountered over a two-year period by a faculty librarian at the Penn State University Libraries while developing and delivering course-related library instruction employing problem-based learning (PBL) in the First-Year Seminar (FYS) of the Penn State School of Information Sciences and Technology (IST). The process of curriculum development involved close cooperation between the school's instructional designers, faculty, and the libraries' faculty. Findings regarding the practical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 9 publications
0
25
0
Order By: Relevance
“…PBL has been used by librarians as a pedagogical 'hook' to create opportunities to embed information literacy development within the curriculum and this has led to extended librarian-faculty collaboration (Fosmire & Macklin 2002). PBL pedagogy has been used in librarian-led information literacy classes where students were set problems relating to the use and support of PBL in HE (Pelikan 2004) and clinical problems have been also been used in search skills training sessions (Snowball 1997). Walton & Hepworth (2011) in their study of level one learners found that learnercentred, collaborative and problem-based learning environments were effective in IL teaching.…”
Section: Literature Reviewmentioning
confidence: 99%
“…PBL has been used by librarians as a pedagogical 'hook' to create opportunities to embed information literacy development within the curriculum and this has led to extended librarian-faculty collaboration (Fosmire & Macklin 2002). PBL pedagogy has been used in librarian-led information literacy classes where students were set problems relating to the use and support of PBL in HE (Pelikan 2004) and clinical problems have been also been used in search skills training sessions (Snowball 1997). Walton & Hepworth (2011) in their study of level one learners found that learnercentred, collaborative and problem-based learning environments were effective in IL teaching.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Pelikan describes the library instruction module for a first-year seminar PBL class, finding that despite the additional work for the instruction librarian of designing the instruction and playing the roles of coach, presenter, and facilitator, PBL is "worth the effort" because of the similarities between the goals of PBL and information literacy instruction. 4 Describing the difference between a PBL session and other instructional sessions, Cheney cites more student-instructor-librarian interaction with a clear sense of purpose on the part of the students-they knew exactly how the library session was tied to their research needs. Use content knowledge and intellectual skills acquired at the university to become continual learners.…”
Section: Problem-based Learning (Pbl) Provides the Theoretical Framewmentioning
confidence: 99%
“…Pelikan describes "a bias born of professional culture toward taking on the obvious role of the reference librarian, manifesting as an urge to provide solutions to the research problems faced by the teams." 16 Our roles shift from providing answers in the form of information resources to asking questions that help students stay focused on the problem. Spence describes it this way: "The tutor' s job is to ask provocative questions that guide further research, reduce dead-end explorations, suggest resources, provide examples, and give precise appraisals of performance."…”
Section: Developing the Lesson Planmentioning
confidence: 99%
“…Enger et al (2002) discussed the benefits of incorporating PBL into information literacy sessions and also addressed the challenges inherent with 50 minute one-shot sessions, suggesting that longer sessions and more involvement in the structure of the course would be beneficial. Pelikan (2004) suggests some pragmatic approaches to implementing PBL in the IL setting. He suggests carefully crafting the flow of the session and preselecting the most helpful and useful resources for students to explore.…”
Section: Review Of Literaturementioning
confidence: 99%